The Value of Time is Never the Hand of a Clock: Marcel Proust’s Time Regained, E. M. Forster’s A Room with a View and A View without a Room - Elif Derya Şenduran (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
This study aims at a comparative analysis of the last volume of Marcel Proust’s In Search of Lost Time, Time Regained (1927), and E. M. Forster’s A Room with a View (1908), including its Appendix A View without a Room (1958) to decipher Henri Bergson’s concepts of duration, intuition, elan vital (vital impulse) and Jacques Lacan’s notions of anticipation and retroaction, against the backcloth of modernity and its representations of clock fixated Time. In this framework of analysis, the study draws on Bergson and Lacan’s notions of Time to foreground the inward turn of the characters in the two novels. The article also seeks to find out whether Time is a construct for Lucy, Cecil, and George in A Room with a View and the narrator, Gilberte, Albertine in Time Regained, regarding the gap between past and present. For instance, remodelling, eradication aspects of Time are never negations for the narrator’s creation of Albertine’s image in his memory in Time Regained. Time never eradicates George and Lucy’s shared view that they once achieved in a room in Bertolini Pension in Italy in A View without a Room, despite wartime remodelling of spatiotemporal realms. Ultimately, in both of the novels, the characters experience the social and empirical reality as their present circumstances affect the narration of their past with involuntary memories, producing virtual qualitative multiplicities. Thus, the anticipation emerges within the images of a dark room that resembles the minds of the characters in the two novels.